Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/nature25738
|View full text |Cite|
|
Sign up to set email alerts
|

The Beaker phenomenon and the genomic transformation of northwest Europe

Abstract: Bell Beaker pottery spread across western and central Europe beginning around 2750 BCE before disappearing between 2200–1800 BCE. The forces propelling its expansion are a matter of long-standing debate, with support for both cultural diffusion and migration. We present new genome-wide data from 400 Neolithic, Copper Age and Bronze Age Europeans, including 226 Beaker-associated individuals. We detected limited genetic affinity between Iberian and central European Beaker-associated individuals, and thus exclude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
342
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(378 citation statements)
references
References 59 publications
28
342
0
8
Order By: Relevance
“…The lack of any signal for the immigration of smaller stature from Iberia into Western and Central Europe sheds significant doubt onto the commonly held view that the Bell Beaker culture originated in the Iberian Peninsula. Rather, it is well in line with a Corded Ware-based origin in NW Europe advocated earlier for archaeological (van der Waals 1984; Jeunesse 2014) and most recently for archaeogenetic reasons (Olalde et al 2018;Valdiosera et al 2018). Moreover, given the somatotrophic and probably growth hormone-related effect of unfermented milk (Wiley 2012) or an assumed direct relationship between genes determining tall stature and lactase persistence (Grasgruber et al 2014), the ability to consume raw milk beyond childhood could be another reason for increasing stature in Northern Europe.…”
Section: Stature Variation In the Context Of Current Anthropometricsupporting
confidence: 64%
“…The lack of any signal for the immigration of smaller stature from Iberia into Western and Central Europe sheds significant doubt onto the commonly held view that the Bell Beaker culture originated in the Iberian Peninsula. Rather, it is well in line with a Corded Ware-based origin in NW Europe advocated earlier for archaeological (van der Waals 1984; Jeunesse 2014) and most recently for archaeogenetic reasons (Olalde et al 2018;Valdiosera et al 2018). Moreover, given the somatotrophic and probably growth hormone-related effect of unfermented milk (Wiley 2012) or an assumed direct relationship between genes determining tall stature and lactase persistence (Grasgruber et al 2014), the ability to consume raw milk beyond childhood could be another reason for increasing stature in Northern Europe.…”
Section: Stature Variation In the Context Of Current Anthropometricsupporting
confidence: 64%
“…Based on these features, we regard our method as an adequate and practical tool for screening large numbers of aDNA male samples and related libraries to get a sense of candidates for follow-up analyses. Indeed, aDNA studies have transitioned to the genomic era with single studies sometimes including whole genomes (Damgaard et al, 2018) or genome-wide SNP data (Olalde et al, 2018) from hundreds of individuals. However, most ancient samples carry low proportions of endogenous DNA and the resulting depth of coverage for a given shotgun experiment is often quite low for laboratories working with a finite budget.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of the Bell Beaker in Late Neolithic Europe provides one of the most puzzling examples about settlements patterns and changes in site location choices across the landscape during the third millennium BCE. Indeed, this spread across central and western Europe is frequently perceived as a global and dramatic change marking the transition between the Late Neolithic and the Early Bronze Age, like the recent results of genetic studies have revealed the great mobility of Bell Beaker people (Haak et al, 2015 ;olalde et al, 2018).…”
Section: Introductionmentioning
confidence: 99%